Robot Arm Project Using Raspberry Pi and Servo Motors - Durdona Bekimmetova; Timur Khudaybergenov (Web of Journals Publishing, 2023)
The integration of Raspberry Pi and servo motors has revolutionized robotics, allowing enthusiasts and developers to build diverse projects. One fascinating project is the creation of a robot arm, which offers a practical and educational way to delve into robotics, automation, and programming. In this article, we will discuss the steps to build a robot arm using Raspberry Pi 4 and servo motors.The project involves constructing a robot arm, connecting it to a Raspberry Pi, programming its movements, and controlling it via Python code. It provides an overview of the essential components, the assembly process, the code development, and the application of this project. This article delves into the fascinating world of robotics through the creation of a robot arm using a Raspberry Pi.
Keywords: Raspberry Pi, programming, robot arm, robotics, educational, practical.